2017
DOI: 10.1080/07399332.2017.1337774
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity, sexual risk behavior, and adherence to antiretroviral therapy among women living with HIV: A systematic review

Abstract: Gender inequalities shape the experience of food insecurity among women living with HIV (WLHIV). We systematically reviewed the impact of food insecurity on sexual risk behaviors and antiretroviral therapy (ART) adherence among WLHIV. We included qualitative or quantitative peer-reviewed articles, extracted data in duplicate, and assessed rigor. Seven studies, from sub-Saharan Africa, North America, and Europe, met inclusion criteria. Food insecurity was associated with increased sexual risk through transactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 59 publications
8
75
0
3
Order By: Relevance
“…The significant effect of gender on food insecurity in the current review is in line with the finding of narrative reviews and international food assistance program guidelines in which food insecurity remains a challenge for women across diverse settings[36, 37]. …”
Section: Discussionsupporting
confidence: 70%
“…The significant effect of gender on food insecurity in the current review is in line with the finding of narrative reviews and international food assistance program guidelines in which food insecurity remains a challenge for women across diverse settings[36, 37]. …”
Section: Discussionsupporting
confidence: 70%
“…29 Equally, food insecurity may be associated with discouragement to use ART for PMTCT. 30,31 Chop et al 31 specifically investigated the effect of food insecurity on uptake of ART among HIV-positive women. They found that food insecurity and hunger were common barriers for women to initiate and adhere to ART.…”
Section: Discussionmentioning
confidence: 99%
“…The worry about side effects as a deterrent to taking ART has been reported by other studies that examined determinants of adherence. [31][32][33] They found that HIV positive clients missed antiretroviral doses in order to avoid side effects. Bam et al 33 assessed enablers and barriers of ART adherence and found that 61.9% of non-adherence respondents skipped medication because of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…This high prevalence of HIV/AIDS among women is driven by illiteracy, gender inequalities, and sexual violence, among others. Chop et al (2017) have also argued that socio-economic factors play a significant role in the spread and impact of HIV/ AIDS, particularly among women. These factors include unemployment, food insecurity, and illiteracy, which have also been associated with poor HIV/AIDS-related clinical outcomes.…”
Section: Curriculum Reform and Its Relevancementioning
confidence: 99%
“…These factors include unemployment, food insecurity, and illiteracy, which have also been associated with poor HIV/AIDS-related clinical outcomes. Other researchers have also suggested that cases of susceptibility to HIV/AIDS-related opportunistic infections and poor access to health care are higher among women (Chop et al, 2017). Statistics South Africa (2018) also estimates that 19% of adults (aged 15-49) in South Africa are HIV positive.…”
Section: Curriculum Reform and Its Relevancementioning
confidence: 99%